Opportunities and challenges in screening for childhood sexual abuse. (November 2018) - Sekhar, Deepa L.; Kraschnewski, Jennifer L.; Stuckey, Heather L.; Witt, Pamela D.; Francis, Erica B.; Moore, Ginger A.; Morgan, Paul L.; Noll, Jennie G.
Abstract: Retrospective studies suggest 1 in 4 girls and 1 in 6 boys will experience sexual abuse before 18 years of age, resulting in future morbidity. Successful interventions exist, however, victims are reluctant to disclose. Screening for childhood sexual abuse (CSA) may provide an opportunity to overcome this barrier, yet no current model for universal CSA screening exists. We sought to understand the perspective of key stakeholders on CSA screening through qualitative research. Eight focus groups of 7–10 participants each (n = 62) were conducted from April-September 2016. Stakeholders included school nurses, school teachers, counselors and administrators, pediatric providers, and parents. The interview guide focused on reporting suspected CSA and impressions of a CSA screening tool. Sessions were audiotaped and transcribed. Researchers used qualitative content analysis to develop conceptual categories that related to CSA screening and reporting. Two research team members independently open-coded 20% of the data for interrater reliability (kappa = 0.98) prior to completing the coding process. Three major categories emerged to inform CSA screening. First, early screening (e.g. kindergarten) was preferred. Confidentiality was a concern, specifically privacy in the school-setting. As CSA perpetrators are often known to the child, parental presence in the medical office was also a concern. Finally, refinement of the screening process was discussed starting with routine education on safe touch and defining "normal." Rather than direct questioning, consistent and repeated offering of opportunities to disclose CSA and identification of a trusted adult were suggested. Next steps should involve partnering with evidence-based CSA prevention programs to incorporate and evaluate the aforementioned elements.